STAKEHOLDER ANALYSIS IN THE ASN LEARNING PROGRAM AT THE HUMAN RESOURCES DEVELOPMENT AGENCY OF EAST JAVA PROVINCE - Didiek Dwiyanto; Andi Taufik; Chusaini Mustas (DIA: Jurnal Administrasi Publik, 2023)
ASN in Indonesia is given the opportunity to gain knowledge in accordance with competency development planning at Government Agencies whose purpose is to develop competencies to support the implementation of tasks. Therefore, the East Java Provincial Government together with the Ministry of State Apartur Empowerment and Bureaucratic Reform and the State Administration Institute agreed to form the "East Java Corporate University (CorpU)". The system developed at CorpU is the concept of Merdeka Belajar. The East Java Provincial Government through BPSDM East Java has various work programs to accelerate the implementation of the East Java CorpU, one of which is "ASN Belajar". The purpose of this innovation is an effort to improve the competence of civil servants. The success of the ASN Belajar program is of course supported by stakeholders. This study is to determine the role, relationship, and effectiveness of the role of stakeholders in achieving the performance targets of BPSDM East Java Province. This research is descriptive with a qualitative approach. While collecting data is carried out by means of open interviews, observations, and documents. Furthermore, in determining informants using purposive sampling techniques. This research is in analyzing data using interactive models. As a result, in general, the implementation of the ASN Belajar program has run well in terms of the role, relationship, and effectiveness of stakeholders. Therefore, the successful implementation of the ASN Belajar program organized by BPSDM East Java needs to be maintained. In addition, these good examples need to be replicated by or other bureaucracy.